Incidence, Management, and Prevention of Right Ventricular Perforation by Pacemaker and Implantable Cardioverter Defibrillator Leads. Issue 12 (29th July 2014) - MIGLIORE, FEDERICO; ZORZI, ALESSANDRO; BERTAGLIA, EMANUELE; LEONI, LOIRA; SICILIANO, MARIACHIARA; De LAZZARI, MANUEL; IGNATIUK, BARBARA; VERONESE, MARTA; VERLATO, ROBERTO; TARANTINI, GIUSEPPE; ILICETO, SABINO; CORRADO, DOMENICO
<x xml:space="preserve">Abstract</x> Background Cardiac perforation of the right ventricle (RV) is a rare but potentially life‐threatening complication of both pacemaker (PM) and implantable cardioverter defibrillator (ICD) implant. Appropriate management is still uncertain. We assessed the incidence of subacute (24 hours–1 month) or delayed (>1 month) cardiac perforation by RV lead and the results of percutaneous lead extraction. Method The study population included all patients diagnosed with subacute or delayed RV‐lead perforation during the period 2007–2013. The incidence of perforation according to device type and fixation mechanism was calculated. The outcome of the percutaneous approach, consisting of lead extraction by simple traction, was assessed. Results Cardiac perforation was diagnosed in 14 (eight females, mean age 71 [range 47–83] years) patients out of 3, 815 who received an RV‐lead implant (0.4%). The overall incidence of RV‐lead perforation was similar between ICD (0.3%) and PM (0.4%) implants (P = 1.0) and between active (0.5%) and passive (0.3%) fixation leads (P = 0.3). All perforating leads were originally placed at the RV apex. Five patients were asymptomatic, but all presented altered lead electrical parameters. Surgical removal of the lead was performed in one patient while in the remaining the leads were successfully extracted by direct manual traction in the absence of any complications. In all patients, new active fixation leads were positioned in the RV septum and the follow‐up (42 ± 27 months) was uneventful. Conclusions RV perforation is a rare complication of both PM and ICD implants, regardless of the lead fixation mechanism. In most patients, percutaneous lead extraction is a safe and effective management approach.